(untitled) (The International Journal of Educational Sciences and Arts, 2025)
The education sector is undergoing significant transformations due to digitalization, where technology has become a fundamental component in enhancing the quality of the learning process. This study aims to analyze the role of digitalization in developing teaching methodologies, focusing on its benefits, implementation challenges, and improvement strategies. The study also reviews successful international experiences in digital education, such as Singapore and Finland, while proposing solutions to enhance its adoption in Saudi educational institutions. The research relies on analyzing previous studies, highlighting the importance of digital transformation in achieving sustainable development goals.